Slow English Podcast Challenges untuk Meningkatkan Speaking Skills pada Siswa EFL - Moh. Zainuddin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to enhance students' speaking skills through the English Podcast Challenge activity. Through the English Podcast, students create a video speaking project with a duration of sixty seconds for one day, and this activity is carried out for 1 month utilizing artificial intelligence (AI). The activity was conducted over 14 meetings in four classes of the Informatics Engineering study program. Students were guided using AI technology, such as ChatGPT and Grammarly, to construct logical and contextual English sentences. They were then challenged to produce a one-minute podcast with a coherent, clear, and communicative concept. The research method employed was a descriptive qualitative approach, utilizing data collection techniques that included observation, documentation, assessment rubrics, and student perception questionnaires. The study's results showed a significant increase in aspects of fluency, accuracy, pronunciation, and student confidence. As many as 87.5% of students completed the challenge with good quality, and more than 90% responded positively to the use of AI. This activity has proven effective in developing contextual and creative speaking skills.